Computer or teacher: Who predicts dropout best? - Eegdeman, Irene; Cornelisz, Ilja; van Klaveren, Chris; Meeter, Martijn (Frontiers in Education, 2022)
Machine learning algorithms use data to identify at-risk students early on such that dropout can be prevented. Teachers, on the other hand, may have a perspective on a student’s chance, derived from their observations and previous experience. Are such subjective perspectives of teachers indeed predictive for identifying at-risk students, and can these perspectives help increase the prediction performance of machine learning algorithms? This study puts 9 teachers in an upper secondary vocational education program to the test. For each of the 95 freshmen students enrolled in the program, these teachers were asked whether a student would drop out by the end of their freshman year. Teachers answered this question at the beginning of the program and again after the first ten weeks of the program. Teachers predicted dropout better than the machine learning algorithms at the start of the program, in particular, because they were able to identify students with a very high likelihood of dropout that could not be identified by the algorithms. However, after the first period, even though prediction accuracy increased over time for both algorithms and teachers, algorithms outperformed the teachers. A ranking, combining the teachers composite and the random forest algorithm, had better sensitivity than each separately, though not better precision.